Clinical Hints: Patient Information About Third Molars - Jacobs Stanley G. (Sciendo, 1990)
Kenneth Adamson Department for Orthodontia, The Royal Dental Hospital of Melbourne, 711 Elizabeth Street, Melbourne, Victoria 3000